Leadership in Sport: from Coach to Manager – An Integrative Perspective - CUCUI, Gheorghe Gabriel; CUCUI, Ionela Alina (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
The evolution of leadership roles in sport has generated increasing interest in recent years, especially in the context of professionalization, performance management, and organizational complexity. This theoretical article explores the transition from the traditional role of the coach — as a direct leader of athletic performance to the more complex managerial role, which encompasses strategic planning, communication, decision-making, and team coordination. Starting from a multidisciplinary review of the literature (sports sciences, organizational behavior, and psychology), the paper outlines the conceptual differences and overlaps between coaching and managing in sport environments. An integrative perspective is proposed, emphasizing the fluidity of leadership roles and the importance of adaptive leadership styles. It is argued that modern sport leaders must combine coaching expertise with managerial competence to effectively respond to both athlete’s needs and organizational challenges. The article discusses key factors such as emotional intelligence, transformational leadership, team dynamics, and role conflict in dual-role positions. Furthermore, the paper highlights the increasing need for leadership development programs that target both the technical and managerial dimensions of sport professionals. By synthesizing current theoretical frameworks and research findings, the article aims to contribute to a better understanding of the coach-manager continuum and to support the development of holistic leadership approaches in sport organizations. This integrative approach may offer valuable insights for educators, policy-makers, and practitioners involved in sport leadership development. Article history: Received 2025 August 15; Revised 2025 September 30; Accepted 2025 October 10; Available online 2025 November 20; Available print 2025 November 30